Molecular identification of minnow Opsariichthys hainanensis (Teleostei: Cyprinidae) from the lake Phu Ninh, Quang Nam province - Thien, Huynh Quang; Khanh, Nguyen Van; Chen, I-Shiung (Academia Journal of Biology, 2018)
The fish of genus Opsariichthys was collected from the Lake Phu Ninh (Quang Nam Province) and its taxonomic relation to other species in the same genus was analyzed based on the molecular data of mitochondrial DNA D-Loop region. The result showed that the fish from Quang Nam Province is closely related to its congener, Opsariichthys hainanensis, from Hainan Island (China), but differed from Opsariichthys bidens from mainland China or from Opsariichthys uncirostris from Japan. Citation: Huynh Quang Thien, Nguyen Van Khanh, I-Shiung Chen, 2017. Molecular identification of minnow Opsariichthys hainanensis (Teleostei: Cyprinidae) from the lake Phu Ninh, Quang Nam province. Tap chi Sinh hoc, 39(4): 463-466. DOI: 10.15625/0866-7160/v39n4.8964. *Corresponding author: hqthien@gmail.com Received 5 December 2016, accepted 12 August 2017